Truncation of ADAMTS13 by Plasmin Enhances Its Activity in Plasma - Clark, Chantal C.; Mebius, Mirjam M.; de Maat, Steven; Tielens, Aloysius G. M.; de Groot, Philip G.; Urbanus, Rolf T.; Fijnheer, Rob; Hazenberg, Bouke P.C.; van Hellemond, Jaap J.; Maas, Coen (Thrombosis and Haemostasis, 2018)
ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) cleaves von Willebrand Factor (VWF) multimers to control their thrombogenicity. The fibrinolytic enzyme plasmin can cleave VWF in a similar manner. However, plasmin can also cleave ADAMTS13, which ultimately inactivates it. This leaves the overall role of plasmin in primary haemostasis uncertain.We investigated the combined molecular effects of plasmin on VWF and ADAMTS13. We first identified that plasmin destroys FRETS-VWF73 substrate by cleaving the ADAMTS13 binding region in a buffered system. We next investigated how plasmin affects both VWF and ADAMTS13 under static conditions in plasma by western blotting. We found that globular VWF is largely protected from plasmin cleavage. However, ADAMTS13 is rapidly cleaved under these conditions, suggesting inactivation. Surprisingly, we observed that plasmin enhances ADAMTS13 activity in a modified two-stage FRETS-VWF73 assay that protects FRETS-VWF73 substrate from degradation. In direct binding studies under the same conditions, we found that plasmin generates multiple C-terminally truncated forms of ADAMTS13 with VWF-binding capacity. In an effort to seek evidence for this mechanism in vivo, we analysed plasma from patients with systemic amyloidosis, which is hallmarked by a hyperfibrinolytic state. We found that their plasma contained increased levels of C-terminally truncated forms of ADAMTS13, which correlated with their hyperfibrinolytic state.We propose that truncation of ADAMTS13 by plasmin abolishes intramolecular self-association, which improves interaction with unfolded VWF.
Keywords: ADAMTS13; von willebrand factor; plasmin